Language Choice in Mixed Families of Different Ethrobs in Empus Talu Village - Munthe, Sediken Tara Munthe; Inge Ayudia (Edutech Publishing Media, 2023)
The formulation of the problem studied is what language is chosen, and what factors influence the choice of language in mixed families in Empus Talu Village, Bebesen District, Central Aceh Regency. This research aims to find out what language is chosen in mixed families in Empus Talu Village, Bebebsen District, Central Aceh Regency and also to find out what factors influence the choice of language in mixed families in Empus Talu Village, Bebebsen District, Central Aceh Regency. The research method used is a qualitative research method. The data source in this research is a mixed family, namely the mother and father have different ethnicities. The family lives in the Empus Talu Village area, Kec. Bebesen, Kab. Central Aceh. The data analysis steps in this research are as follows. Data is grouped based on problem formulation, classifying data according to the aspects studied, correcting the results of observation notes, record all data and carry out re-analysis and convey the results according to the problem in descriptive form, and concluding research results. The language chosen by mixed ethnic families in Empus Talu Village, Bebesen District, Central Aceh Regency is generally Indonesian.